The effect of the PjBL learning model on PGSD student's ability in researching natural science - Nita Pratiwi; Haryanto Haryanto; Woro Tri Hastuti (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2021)
This research aims to get information about the effect of the PjBL learning model on PGSD students' ability to research ICT-based science research subjects. This research is an experimental study with a pretest-posttest control group design. The outreach population is all 6th-semester students of the ICT-based Science Research Program at Yogyakarta State University, and the sampling method uses Purposive Sampling. Data analysis uses a Variant Univariate Analysis T-Test on the significance level of 5%. The results showed that the project-based learning model increases positively and significantly towards students' ability and a significant difference of results towards students' ability between the group of students studying in the class with conventional methodology and PjBl methodology.